2002
DOI: 10.1111/1540-6237.00127
|View full text |Cite
|
Sign up to set email alerts
|

One Person—No Vote; One Vote; Two Votes: Voting Methods, Ballot Types, and Undervote Frequency in the 2000 Presidential Election

Abstract: Objectives. Political science long ignored the actual mechanics of voting-until the 2000 presidential contest. This research note offers a systematic empirical inquiry into the potential effects of various voting methods and electorate-specific variables on the rate at which citizens register a preference via the act of voting. Methods. Voting methods were analyzed in relation to the rate of undervotes recorded in Georgia's 159 counties during the 2000 general election using a set of multivariate models. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 1 publication
2
30
0
1
Order By: Relevance
“…A relatively higher rate of overvotes resulting in spoiled ballots was found in precincts with more black residents (Neely and Cook 2008). This follows work that has examined the residual vote (Bullock and Hood 2002;Darcy and Schneider 1989;Kimball et al 2004;Kimball and Kropf 2005) and overvotes, in particular (Sinclair and Alvarez 2004). 5 Higher counts of overvotes were also found, at times, among San Francisco communities with more Latino residents (Neely and Cook 2008), something shown in a similar analysis of voters in Los Angeles (Sinclair and Alvarez 2004), and in areas with more foreignborn residents.…”
Section: Literature and Hypothesesmentioning
confidence: 73%
“…A relatively higher rate of overvotes resulting in spoiled ballots was found in precincts with more black residents (Neely and Cook 2008). This follows work that has examined the residual vote (Bullock and Hood 2002;Darcy and Schneider 1989;Kimball et al 2004;Kimball and Kropf 2005) and overvotes, in particular (Sinclair and Alvarez 2004). 5 Higher counts of overvotes were also found, at times, among San Francisco communities with more Latino residents (Neely and Cook 2008), something shown in a similar analysis of voters in Los Angeles (Sinclair and Alvarez 2004), and in areas with more foreignborn residents.…”
Section: Literature and Hypothesesmentioning
confidence: 73%
“…A relatively higher rate of overvotes resulting in spoiled ballots was found in precincts with more black residents (Neely and Cook 2008). This follows work that has examined the residual vote (Bullock and Hood 2002;Darcy and Schneider 1989;Kimball et al 2004;Kimball and Kropf 2005) and overvotes, in particular (Sinclair and 5 Alvarez 2004). 5 Higher counts of overvotes were also found, at times, among San Francisco communities with more Latino residents (Neely and Cook 2008), something shown in a similar analysis of voters in Los Angeles (Sinclair and Alvarez 2004), and in areas with more foreignborn residents.…”
Section: Literature and Hypothesesmentioning
confidence: 97%
“…However, because those differences were rare in the earlier IRV analysis (Neely and Cook 2008) we expect there to be no significant difference in overvotes between areas with more male or female residents. Other factors have been shown to matter in the rate at which voters cast uncounted ballots: elderly voters (Darcy and Schneider 1989;Kimball and Kropf 2005;Stiefbold 1965), less educated voters (Walker 1966;Bullock and Hood 2002), and poorer voters (Darcy and Schneider 1989;Kimball, Owens, and Keeney 2004;Knack and Kropf 2003) have been identified as more likely to cast a ballot that is not counted. However, the prior IRV study found few of these relationships.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Others propose replacing punch card voting with either mechanical lever machines or optical scans (Bullock and Hood 2002;Knack and Kropf 2003). 3 The 2002 federal Help America Vote Act created a grant program for states that replaces punch card or lever voting machines with computer-based 'touch screen' systems.…”
Section: Introductionmentioning
confidence: 99%